Modified migrating birds optimization algorithm for closed loop layout with exact distances in flexible manufacturing systems - Niroomand, Sadegh; Hadi-Vencheh, Abdollah; Sahin, Ramazan; Vizvari, Bela (Pergamon-Elsevier Science Ltd, 2015)
This paper addresses a new meta-heuristic algorithm to solve a closed loop layout problem. The proposed algorithm applies a modified version of the recently invented migrating birds optimization method. The computational experiments show that in most of the benchmark problems the results obtained from the proposed migrating birds optimization method is better than those obtained by other methods which are published in the literature. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Flexible manufacturing system; Facility layout problem; Closed loop layout; Migrating birds optimization; Meta-heuristic